Absence of Musculocutaneous Nerve: Embryological Basis - Pankaj, Arvind Kumar; Babu, CS Ramesh; Rani, Archana; Rani, Anita; Chopra, Jyoti; Verma, Rakesh Kumar; Kumar, Navneet; Srivastava, Ajay Kumar (Asian Journal of Medical Sciences, 2013)
Variation of brachial plexus characterized by the absence of musculocutaneous nerve in right arm was found during routine dissection of a 54 year old male cadaver. After giving lateral pectoral nerve, rest of the lateral cord continued as lateral root of median nerve. An unusual branch was arising from lateral cord which crossed the axillary artery anteriorly and then divided into two branches. One of these branches joined ulnar nerve and other medial root of median nerve. All the muscles of front of arm were supplied by branches of median nerve. These variations are important for the anesthetists, surgeons, neurologists during surgery and for anatomists during dissection in the region of axilla. DOI: http://dx.doi.org/10.3126/ajms.v3i2.6626 Asian Journal of Medical Sciences 3(2012) 21-24